Perspectives about pandemic influenza and its prophylactic measures among final year pharmacy students in Karachi, Pakistan - Rahim, Najia; Iffat, Wajiha; Shakeel, Sadia; Nazim, Muhammad Iyad; Qazi, Faiza; Rizvi, Mehwish; Nasiri, Iqbal; Bashir, Lubna; Muhammad Khan, Faisal; Yaseen, Hina; Jamshed, Shazia Qasim (Wolters Kluwer - Medknow, 2017)
Aims: In flu pandemics, pharmacy students' knowledge, attitudes, and practices are critical to save patients life. The objective of study was to determine the knowledge of and attitude toward the pandemic influenza among the pharmacy students of Karachi, Pakistan. Settings and Designs: The cross-sectional study was conducted from September to December 2014 by adopting a prevalidated questionnaire distributed to senior pharmacy students (final year) in seven private and public sector universities of Karachi. Materials and Methods: A total of 443 pharmacy students responded the survey. Data regarding sociodemographic characteristics of the students, perceptions, level of knowledge and attitudes toward influenza, and prophylactic measures were collected. Statistical Analysis: To compute the correlation between different variables, data were analyzed using Pearson's Chi-square statistic method. P< 0.05 was considered statistical significance for all analysis. Results: Influenza was identified as a viral disease (n = 423; 95.48%) and 282 (71.2%) students correctly identified it as disease affecting humans and pigs. Textbooks reported as most common source of knowledge (n = 282; 64%). Most common symptoms identified were fever (81.94%), sore throat (64.1%), and nonproductive cough (43.34%). The most common preventive measures were covering nose and mouth (268; 60.5%) and wearing protective coverings (254; 57.3%). Only half of the students correctly reported about the route of administration (180; 40.6%) and strains in vaccine (186; 41.98%). The best time for administration of such vaccine was known by only 156 pharmacy students (35.34%). The majority of the students (82.6%) had no idea about the manifestation of influenza pandemic. Knowledge regarding influenza differed according to gender and institutions differing in their affiliation with tertiary care hospitals. Conclusion: It was observed that knowledge about disease progression, transmission, vaccination, and treatment in pharmacy students, especially those who are not getting clinical training in tertiary care hospitals was limited. There is an urgent need to develop awareness programs to increase knowledge of influenza among clinical pharmacists as they are more susceptible to infections and community as a whole. © 2017 Journal of Pharmacy and Bioallied Sciences | Published by Wolters Kluwer - Medknow.